Stress-Induced Mitochondrial DJ-1: Role of Parkin, Pink1 and VDAC1 - Hewitt, Sarah (Université d'Ottawa / University of Ottawa, 2016)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and is characterized by motor symptoms such as tremor, rigidity, akinesia and postural instability. Approximately 90% of the cases are due to unknown causes however a familial inheritance has been shown for about 10% of cases. Loss-of-function mutations in DJ-1 cause early-onset PD. Originally identified as an oncogene, DJ-1 has since had many functions attributed to it but its major role in the cell seems to be oxidative stress handling. We have previously demonstrated that DJ-1 deficiency results in hypersensitivity of cells to oxidative stress. Additionally, mitochondria from DJ-1 null mice are fragmented and produce more ROS. To better understand the relationship between DJ-1, cell survival and mitochondria, we investigated the possible interaction between DJ-1 and the mitochondrial protein voltage dependent anion channel 1 (VDAC1). Here we show mitochondrial translocation of DJ-1 following oxidative stress in murine embryonic fibroblasts (MEFs) and primary cortical neurons, a process dependent on Pink1 and Parkin. Additionally, we confirm that DJ-1 and VDAC1 interact and that stress-induced mitochondrial translocation of DJ-1 depends on VDAC1. Deficiency of VDAC1 in primary cortical neurons results in decreased survival, increased ROS production following extended stress, fragmented mitochondria and decreased mitochondrial ATP production. We also demonstrate that there is substantially less matrix-localized DJ-1 in VDAC1 deficient cells. Finally, we demonstrate that decreased mitochondria ATP production can signal for DJ-1 translocation to mitochondria. Taken together, we suggest that mitochondrial translocation of DJ-1 is a two-step process. First, a signal, perhaps decreased mitochondrial ATP production, induces DJ-1 translocation to mitochondria. Second, DJ-1 localizes to the matrix in a VDAC1-dependent manner. Our work suggests that stress-induced mitochondrial localization of DJ-1, specifically to the matrix, is regulated by VDAC1 to promote survival possibly by promoting ATP production.